Avaliação de práticas de gestão empresarial de usinas produtoras de etanol de cana-de-açúcar no noroeste paulista face a princípios de sustentabilidade socioambiental - Bueno, Miriam Pinheiro (2015)
To organizations can contribute to sustainability, they should modify its productive processes in global sense. Therefore, should internalize, besides the economic and structural factors, the natural environment and social questions, that is, the principles of social and environmental sustainability. This tendency includes the Brazilian sugar cane ethanol, which has significant impact in the environmental, socials and economic country questions. As shown in some reports about business sustainability and corporative disclosed by the mills with distilleries (ethanol and sugar), part of this sector has utilized instruments whit tendency to the sustainability process, such as certifications SGA, ISO 14.001, Cleaner Production, Lifecycle Review among others. In this scenario, important to Brazil, this study had as objective review the practices of business management of mills whit distilleries attached sugar cane processors in the administrative region of São José do Rio Preto, state of São Paulo, Brazil, given the principles of social and environmental sustainability. For this, it was applied the qualitative methodology, exploratory and descriptive, primary and secondary research by through questionnaires. The results and analyses were performed to correlate the principles, the dimensions and indicators of social and environmental sustainability versus the mills practices, resulting in identification of the trend level of social and environmental sustainability of the mills. It is concluded that more than 40% of the practices of the mills are not aligned, others are aligning and other are aligned whit the principles of social and environmental sustainability. Therefore, almost half of the practices used in the mills are not, actually, whit the tendency to social and environmental sustainability. It is suggested that the mills decide internalize the principles of social and environmental sustainability in its upstream processes downstream of the sugarcane ethanol industry early in the planning conscious design, seen that its today practices, certainly, will have consequences in the future; and that this practices are continuous and favorable to the principles of social and environmental sustainability, therefore, to the life quality of the population and the own mills, in its corporate business management.